2019
DOI: 10.1002/ajmg.a.61462
|View full text |Cite
|
Sign up to set email alerts
|

Growth charts in Kabuki syndrome 1

Abstract: Kabuki syndrome (KS, KS1: OMIM 147920 and KS2: OMIM 300867) is caused by pathogenic variations in KMT2D or KDM6A. KS is characterized by multiple congenital anomalies and neurodevelopmental disorders. Growth restriction is frequently reported. Here we aimed to create specific growth charts for individuals with KS1, identify parameters used for size prognosis and investigate the impact of growth hormone therapy on adult height. Growth parameters and parental size were obtained for 95 KS1 individuals (41 females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The limitation is that it is difficult to predict whether final KS patient growth rate will catch up to that of children not affected by KS. The normal distribution of Body mass index BMI in KS patient groups is much wider than in the general population, which suggests the increased presence of excess weight or even obesity in KS patients [26]. This obesity has been observed starting at the age of 4.…”
Section: Growth and Endocrinologymentioning
confidence: 97%
See 1 more Smart Citation
“…The limitation is that it is difficult to predict whether final KS patient growth rate will catch up to that of children not affected by KS. The normal distribution of Body mass index BMI in KS patient groups is much wider than in the general population, which suggests the increased presence of excess weight or even obesity in KS patients [26]. This obesity has been observed starting at the age of 4.…”
Section: Growth and Endocrinologymentioning
confidence: 97%
“…Another KS patient with a nonfunctional dysplastic kidney underwent successful transplantation at the age of 14 [192]. One KS patient did not undergo renal transplantation in time and died at the age of 5 years due to renal failure and concomitant pulmonary hypertension [26]. Renal hypoplasia characteristics can be seen upon renal ultrasonography and may be associated with increased risk of renal insufficiency.…”
Section: Nephrological Issues In Kabuki Syndromementioning
confidence: 99%
“…A recent study identified a GH deficiency in 13% of subjects with KS1, with a size reduction beyond the predicted one (− 2 SD and − 1.8 SD for males and females, respectively). Interestingly in this study an absent response to GH therapy has been documented [33]. Growth during childhood depends primarily on the GH/IGF-1 axis and thyroid hormones.…”
Section: Discussionmentioning
confidence: 46%
“…Neurodevelopmental profile in our patient with KS1 was characterized by a progressive reduction of OFC and cerebellar vermis hypoplasia concomitant to developmental delay and generalized hypotonia with oromotor dysfunction. Postnatal microcephaly has been reported in 32% of patients with KS1 [33]. Developmental delay and/or intellectual disability have been considered diagnostic criteria in a recent consensus [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation